A Chemotaxonomic Study of Cuticular Hydrocarbons on Epilachna indica (Family: Coccinellidae) from Sarawak - Bosorang, Rizoh; Assim, Zaini; Hanapi, Sulaiman (Borneo Journal of Resource Science and Technology, 2016)
The chemical composition of cuticular hydrocarbons of adult Epilacnha indica (ladybird beetles), collected from Kota Samarahan, Kota Padawan and Lanjak-Entimau, Sarawak were analyzed by using a capillary gas chromatography-mass spectrometer (GC-MS). Cuticular hydrocarbons extracted from 18 samples of adult E. indica (comprise of 90 individuals). Over 95% of the hydrocarbon peak areas consist of chain lengths from C18 to C38 . The proportions of n-alkanes between three different localities are significantly difference, except for ndotriacontane and n-tetratriacontane. Comparison between Kota Samarahan and Kota Padawan samples revealed the significant different in hydrocarbon composition for even-numbered carbon n-alkanes ranging from n-C18 to n-C38 except for n-C32 and n-C34 . Several odd-numbered carbon n-alkanes such as n-C25 , n-C27 , n-C33 and n- C35 also showed significant difference in the composition between Kota Samarahan and Kota Padawan. Examination on components contributing to the differentiation of localities showed that n-C29 , n-C33 and n-C36 were important in discriminating three different localities. Discriminant function analysis (DFA) successfully classified all samples into three correct groups in 100% of cases, with cross-validation resulted in an error of 7.7%. Individuals from each locality were grouped in the range of 2.10 - 9.16% differences, with average of 43% different reflected between localities. E. indica samples collected from the forests containing simpler hydrocarbon pattern than samples collected around housing or industrial areas. Result showed that differences in microenvironment have influenced the composition and proportion of insect cuticular hydrocarbon. The finding reveals the potential of cuticular hydrocarbons profile to separate subpopulations of species.